PENGARUH KEPEMILIKAN ASET, KETERSEDIAAN INFRASTRUKTUR, DAN PENDIDIKAN TERHADAP PENDAPATAN DAN KESEJAHTERAAN RUMAH TANGGA MISKIN - Meidiana, Ni Putu Cahya Agung Tika; Marhaeni, A.A.I.N. (Buletin Studi Ekonomi, 2019)
Abstract: Effect of Asset Ownership, Availability of Infrastructure, and Education on Income and Well-being of Poor Households. The purpose of this research is to know 1) the influence of asset ownership, infrastructure availability, and education on poor household income; 2) Influence of asset ownership, infrastructure availability, education, and income to poor households ' welfare; 3) indirect influence of asset ownership, availability of infrastructure, and education to prosperity through poor household income. The study uses primary and secondary data with Path analysis methods. The study took 81 samples in the East Bali development area, a sample withdrawal per district in the East Bali development area is each of 27 samples. The results concluded that asset ownership was positively influential but insignificant to revenues. The availability of infrastructure has no effect on revenue, while education is positive and significant towards revenue. This reflects that the development of human capital through education is a crucial determinant to lower the number of poor households. Variable asset ownership does not affect welfare, the availability of infrastructure positively affects the welfare, education and income positively and significantly to the welfare.